2017
DOI: 10.1007/s00436-017-5429-7
|View full text |Cite
|
Sign up to set email alerts
|

Ancient parasites from endemic deer from “CUEVA PARQUE DIANA” archeological site, Patagonia, Argentina

Abstract: The narrow Andean-Patagonian temperate rainforest strip in the west of southern South America is inhabited by two endemic species of cervids, the southern pudu (Pudu puda) and the huemul (Hippocamelus bisulcus), both cataloged as near threatened and threatened species, respectively. One of the possible causes of their declined number is the susceptibility to livestock diseases. Significant zooarchaeological records of both deer have been found throughout the Holocene from Patagonia. The present contribution re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 22 publications
1
8
0
3
Order By: Relevance
“…Beltrame et al (2017a, 2017b, 2020) described digenean eggs found in coprolites belonging to endemic deer from Patagonia in pre-Hispanic times. Samples described by Beltrame and collaborators were collected from the archeological site named “Cueva Parque Diana” (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Beltrame et al (2017a, 2017b, 2020) described digenean eggs found in coprolites belonging to endemic deer from Patagonia in pre-Hispanic times. Samples described by Beltrame and collaborators were collected from the archeological site named “Cueva Parque Diana” (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…Among the eggs described by Beltrame et al (2017b), some were identified with the trematodan digenean species Fasciola hepatica (Figure 2). This constituted the first report of digenean eggs from ancient deer worldwide, and confirmed its presence prior to the arrival of European cattle.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Scarcella et al, 2012;Savage et al, 2013;Fuchs et al, 2013). -Coma et al, 2001;Bargues et al, 2017), pero recientes hallazgos paleoparasitologicos locales en fósiles animales con más de 2000 años de antigüedad suponen que este trematodo podría haber llegado antes a América (Beltrame et al, 2017). En efecto, Sey (1991), propuso que rumiantes parasitados por trematodos podría haber migrado desde Eurasia hacia América a través del canal de Bering, y posteriormente al surgimiento del estrecho de Panamá (hace 3 millones de años), haber arribado a América del Sur.…”
Section: Resultsunclassified